'Windows and mirrors' or 'closed doors'? Representations of diversity in early years' textbooks. - O'Toole, Barbara; Moloney, Caoimhe (Irish National Teachers' Organisation, 2018)
This research examined representations of diversity in a sample of early years textbooks. Using critical discourse analysis as a framework, the study examined how particular groups were represented, or, of equal importance omitted, from these books. The scope of the analysis included images and text. The study found significant omissions of particular groups. It identified uncritical tokenistic approaches towards certain groups which functioned to reinforce stereotypes rather than challenge them. The study further identified an assumption that readers were members of the dominant ‘in-group’, an assumption that functioned as exclusionary towards children from minority groups.
Keywords: Diversity; Identity; Representation; Textbooks; Early Years; Education